Tourist Decision to Visit Barbate Date Palm Plantation: Attractions, Location, and Promotion - Nadiya, Nadiya; Fitri, Aida; Marselindo, Rio (Al Mashaadir : Jurnal Ilmu Syariah, 2023)
This study aims to determine the effect of attractiveness, location and promotion on the decision of tourists to visit the Barbate date palm plantation tour in Aceh Besar District. The sample of this research is 96 respondents using ancient formula. Measuring tool used is to use multiple linear regression. The research results produce the following equation: Y = 1.137 + 0.139 X 1 + 0.560 X 2 + 0.104 X 3 + e . The correlation coefficient (R) of 0.139 or 13.9% illustrates that tourist attraction, location and promotion influence visitor decisions Barbate Dates Farm Tour, Aceh Besar District. The coefficient of determination (R2) is 86.3% which indicates that tourist attraction, location and promotion influence visitor decisions Barbate Dates Garden Tourism in Aceh Besar District and 13.7% visitor decision rate Barbate Dates Garden Tourism in Aceh Besar Regency is influenced by variables that are not examined. The results showed that simultaneously and partially attractiveness, location and promotion had a significant effect on the decision of tourists to visit the Barbate date plantation tour, Aceh Besar District .